Germination technique of Pandanus tectorius (Park.) seeds - Ikhsan Matondang; Sri Endarti Rahayu (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
Sea pandanus (Pandanus tectorius Park.) is a living plant whose humans use all parts. This plant has bright prospects to be developed in the future. Ecological benefits as abrasion resistance, wind resistance and tsunami mitigation. The presence of secondary metabolites in pandan fruit and leaves can be used as an ingredient for treatment, and even the leaves can be used in the fibre industry. Propagation of this plant can be done through seeds and cuttings. Cultivation techniques for sea pandanus have been carried out to determine the effect of polybag size and growth media on germination. The success of germination is one of the determinants of plant cultivation success. Sea pandan seeds are recalcitrant seeds, seeds that are difficult to germinate. It is necessary to conduct research related to the acceleration of germination. This study aimed to determine the best soaking time for producing ready-to-plant seeds. This study used a completely randomized design (CRD) with ten replications. Data analysis used the F test, followed by the minor significant difference test (BNT). The duration of soaking fruit/seeds for 1, 2, 3, 4 and 5 days did not differ in germination time. Soaking fruit/seeds for 1, 2, 3, 4 and 5 days showed germination time on days 37, 38, 39, 40 and 41. The seeds' height and root length parameters were not different for all treatments. The treatment of removing part of the fruit mesocarp by soaking for one day can be used for sea pandan seed germination techniques.